Teachers' Readiness, Perceptions, and Use of Generative Artificial Intelligence in Educational Practice - Novia Ayu Lestari; Agus Susanta; Nurul Astuty Yensy (Journal of Social Work and Science Education, 2026)
This study examines teachers’ readiness, usage patterns, perceived benefits, barriers, and professional development needs related to integrating Generative Artificial Intelligence (Gen AI) into educational practice. A quantitative descriptive exploratory survey design was employed. Data were collected via online questionnaires from 80 teachers across multiple educational levels (early childhood to vocational secondary) in Bengkulu. Descriptive statistics and thematic analysis were used to analyse the data. Teachers reported high functional readiness and positive perceptions of Gen AI, particularly for lesson planning and content development, while its application for learning analytics and reflective pedagogical inquiry remained limited. The most significant barriers were lack of training and unclear school policies, whereas teachers did not view Gen AI as a threat to their professional role. Key professional development needs included practical training, ethical guidance, curriculum integration, and peer communities. The study provides empirical evidence on teachers actual pedagogical workflows in a developing‑country context, distinguishing functional readiness from conceptual literacy. Findings offer a clear agenda for policy development and teacher professional learning programmes. The research advances understanding of Gen AI integration in resource‑constrained settings and provides an evidence base for pedagogically grounded, ethically responsible AI adoption in education.